The State and the 1979 Constitution - Blancas Bustamante, Carlos (1981)
This article provides a comprehensive view of the 1979 Constitution of Peru, highlighting its focus on the duties of the State, the form of the State, the concept of labor, sovereignty, social constitutionalism, and how these elements shape the Peruvian political legal framework. Along these lines, the author first focuses on the definition and meaning of the "form of the State", differentiating it from the "form of government". Having delimited this, through excerpts from the constitutional text, he presents the duties of the State, such as the promotion of general welfare, justice, and the elimination of exploitation, reflecting the ideological character of the norm. In this regard, the author discusses the concept of work and presents it as a right and a social duty. On the other hand, he also explores the characteristics of the Peruvian State, defined as representative democratic, social and decentralist unitary, and discusses the classification of the States as unitary or federal, and the distinction between them. Likewise, the article examines the principle of sovereignty, especially popular sovereignty with its limitations, together with social constitutionalism and the incorporation of social and economic rights, which seek to transform liberal democracy into social democracy. With all this in mind, the author reviews the broad recognition of social rights in the Constitution, covering issues such as family, social security, health, education and labor.